2020
DOI: 10.1007/s11064-020-03017-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of a Betaine/GABA Transporter 1 (BGT1) Inhibitor Displaying an Unusual Biphasic Inhibition Profile and Anti-seizure Effects

Abstract: Focal epileptic seizures can in some patients be managed by inhibiting γ-aminobutyric acid (GABA) uptake via the GABA transporter 1 (GAT1) using tiagabine (Gabitril®). Synergistic anti-seizure effects achieved by inhibition of both GAT1 and the betaine/GABA transporter (BGT1) by tiagabine and EF1502, compared to tiagabine alone, suggest BGT1 as a target in epilepsy. Yet, selective BGT1 inhibitors are needed for validation of this hypothesis. In that search, a series of BGT1 inhibitors typified by (1R,2S)-2-((4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Using computationally guided mutagenesis studies we reveal that interactions with the residues Q299 and E52 drive activity and selectivity of bicyclo-GABA and 2 . Since these two residues were already identified as relevant for other compound classes ( Jørgensen et al, 2017 ; Kickinger et al, 2020 ; Lie et al, 2020 ), we conclude that hydrogen bonding between the protonated nitrogen moiety of BGT1 inhibitors and Q299 and E52 is a key feature for selective BGT1 inhibition. Although the synthetic chemistry for producing bicyclo-GABA and 2 is challenging, both compounds constitute relevant tool compounds for further pharmacological investigations, potentially including conversion into (radio)labeled ligands for BGT1 to determine affinities and/or visualize regional and cellular BGT1 localization.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…Using computationally guided mutagenesis studies we reveal that interactions with the residues Q299 and E52 drive activity and selectivity of bicyclo-GABA and 2 . Since these two residues were already identified as relevant for other compound classes ( Jørgensen et al, 2017 ; Kickinger et al, 2020 ; Lie et al, 2020 ), we conclude that hydrogen bonding between the protonated nitrogen moiety of BGT1 inhibitors and Q299 and E52 is a key feature for selective BGT1 inhibition. Although the synthetic chemistry for producing bicyclo-GABA and 2 is challenging, both compounds constitute relevant tool compounds for further pharmacological investigations, potentially including conversion into (radio)labeled ligands for BGT1 to determine affinities and/or visualize regional and cellular BGT1 localization.…”
Section: Discussionmentioning
confidence: 65%
“…In a previous study, we have already identified Q299 and E52 in BGT1 as part of the molecular determinants driving activity and selectivity of a series of cyclic 2-amino-tetrahydropyrimidine/pyridine compounds ( Kickinger et al, 2020 ). We therefore conclude that the interaction between the amino moiety of different BGT1 compound classes with Q299 and E52 is a general key feature for selective BGT1 inhibition ( Jørgensen et al, 2017 ; Kickinger et al, 2020 ; Lie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations